In vitro interaction of bovine herpesvirus 1 with uterine tube epithelial cells and oocytes - Gonçalves, Roseli Fernandes; Soares, Rodrigo Martins; Orlandi, Cássia Maria Barroso; Richtzenhain, Leonardo José; Visintin, José Antonio; D'angelo, Magali (Instituto Biológico, 2015)
The aims of this study were to assess in vitro if bovine oocytes and oviductal epithelial cells from slaughterhouses for in vitro fertilization use may be infected with bovine herpesvirus 1; to analyze whether the treatment with trypsin according to the International Embryo Transfer Society guideline is efficient to inactivate the bovine herpesvirus 1; to morphologically study the virus-oocyte interaction through optical microscopy. In this study, Madin Darby Bovine Kidney (MDBK) cells that were co-cultured with oocytes matured in vitro and exposed to bovine herpesvirus 1 showed a cytopathic effect. The nested polymerase chain reaction for the supernatant was positive for the bovine herpesvirus 1, thus suggesting that the cytopathic effect observed in the MDBK monolayer was seen due to virus replication and not because of any culture toxicity. It was also observed cytopathic effect and positive nested polymerase chain reaction in MDBK cells co-cultured with in vitro maturated oocytes free of virus, but that were co-cultured in uterine epithelial cells pre-infected with bovine herpesvirus 1 and washed or not with trypsin, demonstrating an oocyte contamination by the virus. When trypsin-washing efficacy was evaluated, we could observe that the trypsin treatment was not able to eliminate the bovine herpesvirus 1 of the oocytes, and it was not observed any morphological difference in the infected oocytes.

RESUMO Os objetivos do presente estudo foram avaliar in vitro se oócitos bovinos e células epiteliais de oviduto provenientes de abatedouros para uso em fertilização in vitro podem ser infectados com o herpesvírus bovino tipo 1; analisar se o tratamento com tripsina padronizado pelo International Embryo Transfer Society é eficiente para inativar o herpesvírus bovino tipo 1; estudar morfologicamente a interação vírus e oócito pela microscopia óptica. Neste estudo, as células Madin Darby Bovine Kidney (MDBK), que foram cocultivadas com oócitos maturados in vitro e expostos ao herpesvírus bovino tipo 1, apresentaram efeito citopático. A reação em cadeia da polimerase aninhada ao sobrenadante foi positiva para o herpesvírus bovino tipo 1, sugerindo que o efeito citopático observado na monocamada MDBK foi em função da replicação do vírus, mas não devido a qualquer toxicidade da cultura. Também foram mostrados efeito citopático e reação em cadeia da polimerase aninhada positivos em células MDBK cocultivadas com oócitos maturados in vitro isentos de vírus, porém que foram cocultivados em células epiteliais uterinas previamente infectadas com herpesvírus bovino tipo 1, que se lavou ou não com tripsina, demonstrando uma contaminação pelo vírus do oócito. Quando foi avaliada a eficácia de lavagem com a tripsina, foi possível notar que este tratamento não foi capaz de eliminar o herpesvírus bovino tipo 1 dos oócitos, e não foi observada qualquer diferença morfológica nos oócitos infectados.
Interação in vitro do herpesvírus bovino tipo 1 com células epiteliais da tuba uterina e oócitos
Keywords: bovine herpesvirus 1; oocytes; uterine tube epithelial cells; nested polymerase chain reaction; bovine; herpesvírus bovino tipo 1; oócitos; células epiteliais da tuba uterina; reação em cadeia da polimerase aninhada; bovinos